Reconstitution de l'histoire méconnue de la gestion de la petite forêt privée - Émilie Andrieu (Les Cahiers de Framespa)
Despite the recent awareness of the importance of taking into account the history of human practices to understand the structuring factors of biodiversity, few studies have considered precise and spatialized long-term forest historical data. This is particularly true in the case of small private forests, which are the most frequent type of woodlands in France. This study reconstructs and analyses forest management history (deforestation events since 1771 and logging events since 1942) in a group of small private forests in southwestern France